2020
DOI: 10.1111/are.14849
|View full text |Cite
|
Sign up to set email alerts
|

Modelling early growth of the pearl oyster Pteria sterna under pilot‐commercial production

Abstract: The pearl oyster Pteria sterna produces pearls from animals gathered from the wild but spat collection is increasingly unreliable. Therefore, hatchery support is required to supply spat for aquaculture operations. In this study is described the hatchery processes to produce spat of P. sterna in a pilot‐commercial grade. Growth and survival (relative and absolute) are described for the different developmental stages and critical aspects identified. Growth (height and length) was analysed using depensatory hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
1
8
1
5
Order By: Relevance
“…Hatchery‐rearing of larvae and spat has been conducted with certain degree of success in Mexico with Pt. sterna 35–38 and P. mazatlanica , 39,40 and in the Caribbean with P. imbricata 41 . In general, pediveliger larvae settle at 19–21 days of age ( Pt.…”
Section: Pearl Culture and Production Methods In Latin Americamentioning
confidence: 98%
See 3 more Smart Citations
“…Hatchery‐rearing of larvae and spat has been conducted with certain degree of success in Mexico with Pt. sterna 35–38 and P. mazatlanica , 39,40 and in the Caribbean with P. imbricata 41 . In general, pediveliger larvae settle at 19–21 days of age ( Pt.…”
Section: Pearl Culture and Production Methods In Latin Americamentioning
confidence: 98%
“…First, native pearl oyster species have a wide distribution in both the Pacific and Atlantic‐Caribbean coasts, where pearls from these species are recognised for their high quality and value, like those produced by other members of the Pteriidae 19–21,55 . Second, the knowledge in some countries and for some species is abundant in relation to natural spatfall 26–29,32 and hatchery‐production of juveniles 37–41 . Many other scientific studies have identified breeding seasons that ensure, with some certainty, the supply of juvenile oysters for pearl culture operations 70,77,83 .…”
Section: Future Opportunities For Pearl Culture In Latin Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Para sustentar la gametogénesis, esta especie utiliza una combinación de estrategias oportunistas y conservadoras a partir de la energía del alimento en invierno y de las reservas de los tejidos somáticos en primavera (Vite-García y Cáceres-Puig et al 2009). Por el contrario, la reproducción de la especie en condiciones de laboratorio ha sido difícil de controlar (Saucedo 2017;Hoyos-Chairez et al 2020), debido básicamente al desconocimiento que prevalece sobre gran parte de sus requerimientos fisiológicos y nutricionales, los cuales son necesarios para asegurar el óptimo desarrollo de los gametos y más adelante de las larvas cultivadas (Gómez-Robles et al 2013, 2023Hawkyns et al 2014). Estos requerimientos no solo están influenciados por los factores ambientales, sino por la condición de los reproductores (madurez de los gametos), por lo que pueden variar al momento de la primera madurez como macho (protandria) o en los sucesivos cambios macho-hembra-macho que ocurren como parte del hermafroditismo secuencial (Saucedo y Southgate 2008;Gómez-Robles et al 2013).…”
Section: Introductionunclassified